PEDAGOGICAL CONDITIONS OF ACTIVE FORMATION COMMUNICATIVE POSITION OF STUDENTS - Sherbyna, D.V. (Pedagogy of Higher and Secondary Education, 2007)
The article investigates pedagogical condition of formation and development of active communicational position of pupils in teaching and educational process.